2005
DOI: 10.1002/jcb.20446
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of interleukin‐2 receptor α‐mediated signaling pathway induces G1 arrest and apoptosis in human head‐and‐neck cancer cells

Abstract: Overexpression of the interleukin-2 receptor (IL-2R) alpha chain in tumor cells is associated with tumor progression and a poor patient prognosis. IL-2Ralpha is responsible for the high affinity binding of the receptor to IL-2, leading to activation of several proliferative and anti-apoptotic intracellular signaling pathways. We have previously shown that human squamous cell carcinoma of a head-and-neck line (PCI-13) genetically engineered to overexpress IL-2Ralpha exhibit increased transforming activity, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…We found that daclizumab effectively inhibited the proliferation of IL-2Ralpha+ cells, but not the vector control cells (112). The cell cycle distribution pattern differs dramatically between the untreated IL-2Ralpha+ and LacZ cells: while 59% of the IL-2Ralpha+ cells are in G 2 -M phase, 50% of the LacZ cells reside in G 0 -G 1 phase (67,112).…”
Section: Effects On Proliferation and Cell Cyclementioning
confidence: 79%
See 4 more Smart Citations
“…We found that daclizumab effectively inhibited the proliferation of IL-2Ralpha+ cells, but not the vector control cells (112). The cell cycle distribution pattern differs dramatically between the untreated IL-2Ralpha+ and LacZ cells: while 59% of the IL-2Ralpha+ cells are in G 2 -M phase, 50% of the LacZ cells reside in G 0 -G 1 phase (67,112).…”
Section: Effects On Proliferation and Cell Cyclementioning
confidence: 79%
“…We found that IL-2Ralpha+ cells were sensitized by the mAb, but the effect was moderate (112). A possible explanation for the modest effect of daclizumab on the sensitization to the apoptosis-inducing drugs may be linked to the arrest of the cells in G 0 /G 1 after daclizumab treatment (112). Previous reports have shown that arresting cells in G 0 /G 1 confers resistance to multiple apoptotic stimuli (113)(114)(115).…”
Section: Effects On Regulators Of Apoptosismentioning
confidence: 80%
See 3 more Smart Citations